2022
DOI: 10.1002/hbm.25787
|View full text |Cite
|
Sign up to set email alerts
|

Enduring effect of abuse: Childhood maltreatment links to altered theory of mind network among adults

Abstract: Childhood maltreatment (CM) confers a great risk of maladaptive development outcomes later in life, however, the neurobiological mechanism underlying this vulnerability is still unclear. The present study aimed to investigate the long-term consequences of CM on neural connectivity while controlling for psychiatric conditions, medication, and, substance abuse. A sample including adults with (n = 40) and without CM (n = 50) completed Childhood Trauma Questionnaire (CTQ), personality questionnaires, and resting-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 74 publications
0
16
0
Order By: Relevance
“…Palaniyappan and colleagues have proposed that dysfunction of the insula–ACC SN is linked to the psychotic symptoms of SZ by inappropriately allocating salience to irrelevant internal or external stimuli [ 68 ]. Reduced FC within brain regions involving the ACC and insula was proven to be associated with heightened affective and anxiety symptoms and an increased risk of developing psychiatric disorders [ 69 , 70 ]. Incentive valence, behavioral relevance, or expectancy violation would determine the processing the stimulus salience of momentary reward and lead to a change in the brain state [ 68 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Palaniyappan and colleagues have proposed that dysfunction of the insula–ACC SN is linked to the psychotic symptoms of SZ by inappropriately allocating salience to irrelevant internal or external stimuli [ 68 ]. Reduced FC within brain regions involving the ACC and insula was proven to be associated with heightened affective and anxiety symptoms and an increased risk of developing psychiatric disorders [ 69 , 70 ]. Incentive valence, behavioral relevance, or expectancy violation would determine the processing the stimulus salience of momentary reward and lead to a change in the brain state [ 68 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…The MFG was a major part of the default mode network (DMN). The DMN is a key network in MDD and plays the role of cognitive control and integrating information (Yeshurun et al, 2021;Liu et al, 2022;Pang et al, 2022b). According to the prevalent triple network model, the symptoms of depression can be explained by dysfunction between the DMN, salience network, and central executive network, especially the increased FC in the DMN (Hamilton et al, 2015;Kaiser et al, 2015;Li et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The 5‐Likert scale was used for responses ranging from 1 (never correct) to five (usually correct). The five sub‐scales have their specific question items, using the previously mentioned five‐level evaluation indicators, and the score of each subscale is between 5 and 25 points (Pang, Zhao, et al, 2022). When the subscale score exceeds a certain threshold value (emotional abuse ≥13, emotional neglect ≥15, sexual abuse ≥8, physical abuse ≥10, physical neglect ≥10), childhood trauma is considered moderate to severe (Bernstein et al, 1994).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies reported that CM was associated with abnormal functional connectivity (FC) within salience network (SN) and between the default mode network and SN (Marusak et al, 2015). Individuals with CM showed increased FC within theory of mind network which was associated with the severity and type of abuse (Pang, Zhao, et al, 2022; Pruessner et al, 2019; Stanton et al, 2020). Furthermore, adults with CM showed increased amygdala connectivity with the hippocampus and prefrontal cortex during emotion processing (Jedd et al 2015).…”
Section: Introductionmentioning
confidence: 99%